2016
DOI: 10.1002/pro.3071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of circular permutation on the structure and function of type 1 blue copper center in azurin

Abstract: Type 1 copper (T1Cu) proteins are electron transfer (ET) proteins involved in many important biological processes. While the effects of changing primary and secondary coordination spheres in the T1Cu ET function have been extensively studied, few report has explored the effect of the overall protein structural perturbation on active site configuration or reduction potential of the protein, even though the protein scaffold has been proposed to play a critical role in enforcing the entatic or "rack-induced" stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…In a previous study, two construct have been built for circular permutation in Az. 27 The mutants, cpAz1 and cpAz2, maintain typical T1C spectroscopic properties, suggesting the robustness of Az structure. However, as the metalbinding loop harbors 3 ligands of copper center, the question remains whether circular permutation will perturb the copper center.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a previous study, two construct have been built for circular permutation in Az. 27 The mutants, cpAz1 and cpAz2, maintain typical T1C spectroscopic properties, suggesting the robustness of Az structure. However, as the metalbinding loop harbors 3 ligands of copper center, the question remains whether circular permutation will perturb the copper center.…”
Section: Introductionmentioning
confidence: 94%
“…2B, here we applied circular permutation strategy, to connect N-and C-termini with a linker GIPGG and create new termini at Gly116 (N-terminus) and Phe114 (C terminus), similar to what have been reported for cpAz1 and cpAz2. 27 The Az-loop mutant was constructed by overlap-extension PCR. The protein was puried in a procedure similar to that of the WT protein 28 to obtain metal-free apo protein with a yield of $40 mg L À1 .…”
Section: Design Of Circularly Permutated Az Variantmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The rst two types of centers share the cupredoxin fold and the interesting feature that all but one of the coordinating amino acids are located in a single loop that connects two b-strands. 1,4 Therefore, along with point mutations, replacement of the entire ligand loop by sequences from other proteins or unnatural sequences, 5 has become one of the preferred strategies for modulating the electronic properties of T1 4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and Cu A sites. [24][25][26][27][28][29][30] This methodology has also allowed for the successful insertion of Cu A sites into the scaffold of T1 [31][32][33][34][35] proteins and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Yu et al (2017) also reported the successful CP of azurin, one of type 1 copper proteins with important roles in electron transfer in diverse biological systems. However, there has been no reports of CP of tyrosinases such as BmTy which have a binuclear type 3 copper center located at the core of a four-helical bundle (Sendovski, Kanteev, Ben-Yosef, Adir, & Fishman, 2011).…”
mentioning
confidence: 99%